Cancer risk in patients with Parkinson's disease in South Korea: A nationwide, population-based cohort study. (August 2019) - Park, Joo-Hyun; Kim, Do-Hoon; Park, Yong-Gyu; Kwon, Do-Young; Choi, Moonyoung; Jung, Jin-Hyung; Han, Kyungdo
Abstract: Introduction: The association between Parkinson's disease (PD) and cancer development is controversial, especially in Asia. Therefore, we conducted a nationwide population-based cohort study to assess the overall cancer risk and risk for specific cancers in patients with PD in Korea. Methods: Using data from the Korean National Health Insurance Database, we analysed 52, 009 patients diagnosed with PD between 2010 and 2015 and 260, 045 individuals without PD. Patients previously diagnosed with cancer were excluded. The age- and sex-matched cohorts were followed up until 2016 for cancer development. Cox proportional hazards regression models were used to evaluate the relationship between PD and cancer. Results: Patients with PD had a lower overall cancer risk (hazard ratio [HR], 0.78; 95% confidence interval [CI], 0.74–0.82) after adjustment for multiple covariates during 2, 022, 852.6 person-years of follow-up. Patients with PD showed significantly lower risk of laryngeal cancer (HR, 0.45; 95% CI, 0.21–0.84), gastric cancer (HR, 0.72; 95% CI, 0.63–0.82), colorectal cancer (HR, 0.675; 95% CI, 0.60–0.76), liver cancer (HR, 0.80; 95% CI, 0.67–0.95), pancreatic cancer (HR, 0.75; 95% CI, 0.62–0.91), lung cancer (HR, 0.73; 95% CI, 0.63–0.84), leukaemia (HR, 0.49; 95% CI, 0.24–0.89), uterine cervical cancer (HR, 0.64; 95% CI, 0.40–0.99) and prostate cancer (HR, 0.78; 95% CI, 0.66–0.91). Conclusion: This nationwide population-based cohort study revealed that patients with PD had lower overall cancer risk and lower risk of specific cancers. Contrary to the results of the recent Asian study, this large cohort study revealed that patients with PD were less likely to develop cancer than those without PD in Korea. Our results were consistent with those of previous Western studies, despite differences in ethnicity and environment. Highlights: Patients with Parkinson's disease (PD) had a lower overall cancer risk than those without PD. Patients with PD showed lower risk of colorectal cancer, gastric cancer, liver cancer, and pancreatic cancer. They also showed lower risk of lung cancer, prostate cancer, laryngeal cancer, leukaemia and uterine cervical cancer. Despite environmental, ethnic and socioeconomic differences, our results were consistent with previous Western studies. Further studies are required to investigate the underlying mechanism of the association between PD and cancer.